2019
DOI: 10.1093/ecco-jcc/jjz204
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Increased Risk of Lymphoma by Thiopurines or Biologics in Japanese Patients with Inflammatory Bowel Disease: A Large-Scale Administrative Database Analysis

Abstract: Background and Aims Patients with inflammatory bowel diseases may have higher incidences of non-melanoma skin cancers and non-Hodgkin lymphoma, potentially linked to underlying disease and treatments. This analysis assessed incidence rates of these malignancies in Japanese patients with ulcerative colitis or Crohn’s disease, and their association with thiopurine and/or anti-tumor necrosis factor-α treatment, using data from a nationwide administrative database in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 31 publications
4
35
1
Order By: Relevance
“…No patient developed lymphoma, leukemia, or skin cancer during the follow-up period, while in Western countries, the risk of lymphoma is reportedly high, especially in patients on thiopurine [ 21 ]. Racial differences may exist in terms of lymphoma susceptibility; our findings may be consistent with those of previous studies [ 9 , 22 ]. A retrospective survey showed only 12 (0.11%) of the 10,500 Japanese patients with UC experienced hematologic malignancies [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No patient developed lymphoma, leukemia, or skin cancer during the follow-up period, while in Western countries, the risk of lymphoma is reportedly high, especially in patients on thiopurine [ 21 ]. Racial differences may exist in terms of lymphoma susceptibility; our findings may be consistent with those of previous studies [ 9 , 22 ]. A retrospective survey showed only 12 (0.11%) of the 10,500 Japanese patients with UC experienced hematologic malignancies [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective survey showed only 12 (0.11%) of the 10,500 Japanese patients with UC experienced hematologic malignancies [ 9 ]. Another recent large-scale study, using a nationwide administrative database in Japan, also reported only 103 (0.14%) cases of Non-Hodgkin lymphoma in 75,673 patients with UC with no increase in the incidence of lymphoma among patients on thiopurines [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients or their caregivers also administered SC injections during the scheduled clinic visits at Weeks 14,22,30,38,46, and 50, under the supervision of the HCP, to allow continued observation of injection technique and adverse events (AEs); while all other scheduled SC injections occurred outside of the clinic. All intravenous (IV) infusions were administered by a HCP during clinic visits at Weeks 6,14,22,30,38,and 46. HCPs had appropriate monitoring and treatment for hypersensitivity reactions available for use following administration of study drug.…”
Section: Subcutaneous Administration Of Vedolizumab Andmentioning
confidence: 99%
“…For example, a recent administrative database analysis of Japanese patients with IBD found no increase in the incidence of non-Hod gkin lymphoma attributable to thiopurine treatment. 14 However, cohort studies in European patients with IBD reported an association between thiopurine treatment and an increased risk of lymphoproliferative disorders or cancer. 15,16 It remains to be determined whether the efficacy and safety of vedolizumab SC differs between patients with UC from Japanese and global populations.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] Of those, seven included lymphoma as a separate composite outcome. 20,21,23,[25][26][27][28] Two of the seven studies had no cases of lymphoma appreciated in the ATA monotherapy group. 22,24 Of those studies that looked at lymphoma as a composite outcome and had cases in a setting of ATA monotherapy, none appreciated an increased risk of lymphoma.…”
Section: Lymphoma As Composite Outcomementioning
confidence: 99%